COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA DI RUPAT UTARA KABUPATEN BENGKALIS - Adi Putra; Hasim As’ari; Adianto Adianto (Journal Publicuho, 2022)
This paper discusses the collaborative governance tourism strategy in developing tourist objects in North Rupat. Potential tourism objects in North Rupat are marine tourism, historical tourism, cultural tourism and nature tourism. In its implementation there are problems such as abrasion, garbage, and accessibility. This study uses a descriptive qualitative method. The research location was conducted in North Rupat. Data collection techniques by observation and in-depth interviews. The data analysis technique uses the opinion of Miles Huberman and Saldana (2014) through stages; data compaction, data presentation (data display), and drawing conclusions or verification (conclusion drawing and verification). The results of this study are that there is tourism potential in every village in North Rupat Subdistrict. The implementation of collaborative governance tourism is Principled Engagement, Shared Motivation, Capacity for Joint Action. Obstacles in implementing collaborative governance tourism are limited human resources, tourism development coordination is implemented simultaneously.